PROFEAT Update: A Protein Features Web Server with Added Facility to Compute Network Descriptors for Studying Omics-Derived Networks. Issue 3 (3rd February 2017) - Zhang, P.; Tao, L.; Zeng, X.; Qin, C.; Chen, S.Y.; Zhu, F.; Yang, S.Y.; Li, Z.R.; Chen, W.P.; Chen, Y.Z.
Abstract: The studies of biological, disease, and pharmacological networks are facilitated by the systems-level investigations using computational tools. In particular, the network descriptors developed in other disciplines have found increasing applications in the study of the protein, gene regulatory, metabolic, disease, and drug-targeted networks. Facilities are provided by the public web servers for computing network descriptors, but many descriptors are not covered, including those used or useful for biological studies. We upgraded the PROFEAT web serverhttp://bidd2.nus.edu.sg/cgi-bin/profeat2016/main.cgi for computing up to 329 network descriptors and protein–protein interaction descriptors. PROFEAT network descriptors comprehensively describe the topological and connectivity characteristics of unweighted (uniform binding constants and molecular levels), edge-weighted (varying binding constants), node-weighted (varying molecular levels), edge-node-weighted (varying binding constants and molecular levels), and directed (oriented processes) networks. The usefulness of the network descriptors is illustrated by the literature-reported studies of the biological networks derived from the genome, interactome, transcriptome, metabolome, and diseasome profiles. Graphical Abstract: Highlights: It computes the currently most comprehensive (up to 329) network descriptors. It supports five network types with different biological representations. It is user-friendly with simple input/output and easy operation. This paper discussed the applications of network descriptors in systems biology. PROFEAT could facilitate the functional investigations of biological networks.